2011
DOI: 10.1007/s12017-011-8163-9
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing Reveals Regional Differences of the α-Synuclein Methylation State Independent of Lewy Body Disease

Abstract: The α-synuclein gene (SNCA) plays a major role in the aetiology of Lewy body disease (LBD) including Parkinson's disease (PD). Point mutations and genetic alterations causing elevated gene expression are causally linked to familial PD. To what extent epigenetic changes play a role in the regulation of α-synuclein expression and may contribute to the aetiology of sporadic LBD is a matter of debate. We analysed the methylation state of the promoter region and a CpG-rich region of intron 1 of α-synuclein in sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 45 publications
5
49
1
1
Order By: Relevance
“…However, epidemiological evidence linking such obsessive behaviors to PD pathogenesis is still lacking. Contrary to the study by Jowaed et al [23], a highresolution methylome study detected no difference in overall methylation at intron 1 of the SNCA gene compared to controls [29]. However, significant differences in hyper-and hypomethylation patterns existed in single CpG analysis at different points with little functional consequence of the formation of 5-methylcytosine emerging from the study.…”
Section: Epigenetic Modulation In Familial Parkinson's Diseasecontrasting
confidence: 84%
“…However, epidemiological evidence linking such obsessive behaviors to PD pathogenesis is still lacking. Contrary to the study by Jowaed et al [23], a highresolution methylome study detected no difference in overall methylation at intron 1 of the SNCA gene compared to controls [29]. However, significant differences in hyper-and hypomethylation patterns existed in single CpG analysis at different points with little functional consequence of the formation of 5-methylcytosine emerging from the study.…”
Section: Epigenetic Modulation In Familial Parkinson's Diseasecontrasting
confidence: 84%
“…confirmed significant increase in SNCA mRNA levels in individual dopamine neuron from idiopathic PD brains using laser capture microdissection, implying a significant transcriptional de-regulation in pathologic conditions6. Moreover, recent progress in research on epigenetic influences on SNCA transcription revealed that hypomethylation of SNCA regulatory region play a significant role towards its higher expression in idiopathic PD789.…”
mentioning
confidence: 79%
“…This particular feature is extremely relevant in studying SNCA expression, as this gene has been shown to get extensively regulated by its epigenetic structure789. Moreover, α-SYN is a molecule whose level of expression is directly correlated with the severity of the PD pathogenesis, thus making this tool very helpful for developing potential therapeutic options2346.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the authors found that the level of maintenance methyltransferase DNMT1 was significantly decreased in the cortex of both groups of patients, which might have resulted in the global hypomethylation in patient groups (Desplats et al , 2011). The next report which came in 2011 described the status of SNCA intron1 methylation in post-mortem Lewy Body Disease brains using the Next Generation Sequencing (NGS) platform (de Boni et al , 2011). The investigators had detailed information about the patients including Braak staging information for the disease.…”
Section: Regulation Of α-Synuclein Expression and Parkinson’s Diseasementioning
confidence: 99%